2006
DOI: 10.5194/acp-6-3315-2006
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and mineralogical composition of different Saharan mineral dust samples: a laboratory study

Abstract: Abstract. In aerosol chamber experiments optical properties of resuspended mineral dust samples of defined size distributions were measured. Extinction coefficients (b ext ) and mass specific extinction cross sections (σ ext ) were determined for Saharan dust samples from different locations. The results for σ ext were not very sensitive to the type of dust and varied at λ=550 nm between 3.3±0.4 m 2 g −1 and 3.7±0.4 m 2 g −1 .The absorption coefficients (b abs ) and mass specific absorption cross sections (σ a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
150
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(162 citation statements)
references
References 16 publications
11
150
1
Order By: Relevance
“…Contrary to the MAE values, there is no statistically significant size dependence of the AAE values, ranging from 2.5 (±0.2) to 4.1 (±0.3), with an average of 3.3 (±0.7), for the PM 10.6 size fraction and between 2.6 (±0.2) and 5.1 (±0.4), with an average of 3.5 (±0.8), for the PM 2.5 fraction. Our values are in the range of those published in the literature (Fialho et al, 2005;Linke et al, 2006;Müller et al, 2009;Petzold et al, 2009;Yang et al, 2009;Weinzierl et al, 2011;Moosmüller et al, 2012;Denjean et al, 2016b), shown in Table 5. AAE values close to 1.0 are found for urban aerosols where fossil fuel combustion is dominant, while AAE values for brown carbon from incomplete combustion are in the range of 3.5-4.2 (Yang et al, 2009;Chen et al, 2015;Massabò et al, 2016).…”
Section: Spectral and Size Variability Of The Mass Absorption Efficiencysupporting
confidence: 75%
See 3 more Smart Citations
“…Contrary to the MAE values, there is no statistically significant size dependence of the AAE values, ranging from 2.5 (±0.2) to 4.1 (±0.3), with an average of 3.3 (±0.7), for the PM 10.6 size fraction and between 2.6 (±0.2) and 5.1 (±0.4), with an average of 3.5 (±0.8), for the PM 2.5 fraction. Our values are in the range of those published in the literature (Fialho et al, 2005;Linke et al, 2006;Müller et al, 2009;Petzold et al, 2009;Yang et al, 2009;Weinzierl et al, 2011;Moosmüller et al, 2012;Denjean et al, 2016b), shown in Table 5. AAE values close to 1.0 are found for urban aerosols where fossil fuel combustion is dominant, while AAE values for brown carbon from incomplete combustion are in the range of 3.5-4.2 (Yang et al, 2009;Chen et al, 2015;Massabò et al, 2016).…”
Section: Spectral and Size Variability Of The Mass Absorption Efficiencysupporting
confidence: 75%
“…The former is lower than the value of 99 × 10 −3 m 2 g −1 that we obtain by extrapolating our measurement at 375 nm. Likewise, our values for the Morocco sample are higher than reported by Linke et al (2006) at 266 and 660 nm. Conversely, the agreement with the estimates of Yang et al (2009) for mineral dust locally re-suspended in Xianghe, near Beijing (China), is very good at all wavelengths between 375 and 880 nm.…”
Section: Spectral and Size Variability Of The Mass Absorption Efficiencycontrasting
confidence: 54%
See 2 more Smart Citations
“…Assuming a classical density value of 2.5 g cm −3 for spherical dust particles (Dulac et al, 1989;Zender et al, 2003;Linke et al, 2006), V g is thus about 0. 0076, 0.19, 0.76, 3.0, 6.8, and 19 cm s −1 for particles of 1,5,10,20,30, and 50 µm in diameter, respectively, implying a downward transport ranging from about 6.6 to 16 400 m d −1 .…”
Section: Discussion Related To Dust Sedimentationmentioning
confidence: 99%